2021
DOI: 10.1111/birt.12567
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rated health before pregnancy and adverse birth outcomes in Sweden: A population‐based register study

Abstract: Background: Poor self-rated health (SRH) at time of childbirth has been associated with adverse birth outcomes. However, it is not known whether prepregnancy SRH contributes to these outcomes or whether SRH is a proxy for some other factors.Therefore, the purpose of this study was to explore the associations between poor SRH before pregnancy and adverse birth outcomes. In addition, maternal characteristics associated with SRH before pregnancy were explored. Methods: A population-based register study encompassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…A previous study exploring poor SRH prior to pregnancy concluded that the rating was largely characterized by a history of psychiatric care. [18] In line with this, women who received psychiatric care during pregnancy in the present study were more likely to have a negative childbirth experience. However, severity and type of psychiatric disorder treated during pregnancy were unknown.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A previous study exploring poor SRH prior to pregnancy concluded that the rating was largely characterized by a history of psychiatric care. [18] In line with this, women who received psychiatric care during pregnancy in the present study were more likely to have a negative childbirth experience. However, severity and type of psychiatric disorder treated during pregnancy were unknown.…”
Section: Discussionsupporting
confidence: 79%
“…Poor SRH was defined as ratings of 'very poor', 'poor' or 'neither good nor poor', whereas good SRH was defined as ratings of 'good' or 'very good', in line with previous studies. [17,18] Further, history of psychiatric care (n/y), pre-gestational medical disorder (n/y) and in vitro fertilisation (IVF, [n/y]) were included. History of psychiatric care was retrieved from the midwife's registration at first antenatal visit using predefined checkboxes in EMR.…”
Section: Pre-gestational Variablesmentioning
confidence: 99%
“…One study found that self‐rated health can induce feelings of being normal but also increase perceptions of pregnant‐related risk and concerns of being judged by the midwife 26 . Furthermore, poor self‐rated health before pregnancy has been largely characterized by a history of psychiatric care and was associated with small‐for‐gestational‐age children and preterm birth 27 . Studies of poor self‐rated health among pregnant women found symptoms of depression and stress, health diagnoses, high body mass index, 28 low birthweight or preterm infants 29 .…”
Section: Discussionmentioning
confidence: 99%
“… 26 Furthermore, poor self‐rated health before pregnancy has been largely characterized by a history of psychiatric care and was associated with small‐for‐gestational‐age children and preterm birth. 27 Studies of poor self‐rated health among pregnant women found symptoms of depression and stress, health diagnoses, high body mass index, 28 low birthweight or preterm infants. 29 Conversely, higher self‐rated health in pregnancy predicted fewer childbirth complications and lower odds of cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, given that few participants in this study reported very poor or poor SRH, we merged the very poor, poor, and neither good nor poor into poor SRH. Such classification of SRH has been used in previous studies …”
Section: Methodsmentioning
confidence: 99%